Penyebab Kasus Sukuk yang Nyaris Gagal Bayar di Abad ke-21 dan Mekanisme Penyelamatannya - Swandaru, Randi; Muneeza, Aishath (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
This study aims to examine the reasons that triggered sukuk to nearly default in the 21st century and the rescue mechanisms they used under the circumstance. This research is constructed as a case study examining selected near default sukuk cases from across jurisdictions. It is found that the main issues that triggered sukuk to nearly default are the lack of development of shariah governance, the backwardness in harmonizing shariah standards, and poor risk management through the business cycle of the underlying project.  It is also found that two main rescue mechanisms are used in handling the sukuk that nearly defaulted. The first way is using commodity murabaha to pay out ijarah sukuk holders, as in the case of Ingress sukuk. The second way is by altering the terms of mudharabah sukuk to accommodate the aspiration of the sukuk holders, as in the case of Dana Gas sukuk. An anomaly in this regard is observed in Nakheel's case, where no restructuring effort was conducted as the Emirate of Dubai covered some of the debts.